Creative Mathematics - Wall, H. S. (Classroom resource materials., 2012)
"Professor H.S. Wall wrote Creative Mathematics with the intention of leading students to develop their mathematical abilities, helping them learn the art of mathematics, and teaching them to create mathematical ideas. Creative Mathematics, according to Wall, "is not a compendium of mathematical facts and inventions to be read over as a connoisseur of art looks over paintings. It is, instead, a sketchbook in which readers try their hands at mathematical discovery." The book is self-contained and assumes little formal mathematical background on the part of the reader. Wall is earnest about developing mathematical creativity and independence in students. Wall developed Creative Mathematics over a period of many years of working with students at the University of Texas at Austin. In fewer than 200 pages, he takes the reader on a stimulating tour starting with numbers and then moving on to simple graphs, the integral, simple surfaces, successive approximations, linear spaces of simple graphs, and concluding with mechanical systems. The student who has worked through Creative Mathematics will come away with heightened mathematical maturity."--Page 4 of cover.